Ukrainian Sunflower Market on the Background of EU and US Markets - Tetyana Kuts; Oksana Makarchuk (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
This paper aims to provide market analysis of the sunflower market in Ukraine (UA) and research the existence of integration between the sunflower oil markets in Ukraine, the European Union (EU) and the United States (US). To fulfill the aims in the paper, yearly balances of sunflower seed, sunflower oil and sunflower cake were analyzed and price analysis was conducted. Price integration was assessed with the use of the error correction model (ECM) which was applied to monthly prices for sunflower oil from 2000 to 2020. Our findings provide evidence of high price transmission between the UA and EU markets, conversely lower price transmission was observed between the UA and the US.